HAD HARGREAVES METHOD FOR EFFECTIVENESS POWER IN PHOTOVOLTAIC MODULE - Roy Pranata Keliat; Solly Aryza; Siti Anisah (INFOKUM, 2022)
Universitas Pembangunan Panca Budi is one of the best locations for solar radiation data collection and it is easy to conduct continuous research on solar cell power plants so that they can develop something in the photovoltaic module. This study discusses a photovoltaic analysis research using the Hargreaves model in terms of predicting the solar radiation that will be obtained and getting the value of effectiveness and efficiency. This study was conducted in a 2022 study in Medan, North Sumatra.